Serotonergic-like profile of 4-propyl-2H-benzo[h]-chromen-2-one (FCS-304) in mice and rats - MORENO, Laura M.; CUCA, Luis Enrique; GUERRERO, Mario F. (Vitae, 2019)
Background: 4-propil-2H-benzo[h]-cromen-2-ona (FCS-304) is a semisynthetic coumarin with MAO-A inhibitory activity and positive results in forced swimming and tail suspension test in mice, but until now, it has not been studied in other screening antidepressant models in mice and rats. Objectives: The aim of this work was to assess the serotonin like effect of FCS-304 in the 5-hydroxytryptophan (5-HTP) test in mice, in the behavioral despair test in rats, and in the reserpine test in rats. Methods: Potentiation of 5-HTP (100 mg/kg, i.p.), induced head twitches were assessed in mice, previously treated with FCS-304 (50-75-150 mg/kg, p.o.). The behavioral despair test was performed in rats treated with FCS-304, recording the immobility time attained by the animals subjected to forced swimming. Antagonism of reserpine-induced ptosis was examined in rats, assessing the level of palpebral closure. Imipramine (30 mg/kg, p.o.) and vehicle (canola oil) served as positive and negative controls, respectively. Results: FCS-304 significantly potentiated 5-HTP induced head twitches in mice, in a dose dependent manner. In rats, FCS-304 significantly decreased the immobility time in the behavioral despair test and antagonized reserpine induced ptosis. Conclusions: These results add support to propose that FCS-304 could elicit antidepressant effects related to MAO-A inhibitory activity.